St. Vincent and the Grenadines : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 1999)
This 1999 Article IV Consultation highlights that during 1990-98, St. Vincent and the Grenadines' real annual GDP growth and inflation averaged 4 percent and 3 percent, respectively. Tourism's importance to the economy grew, and agriculture's fell, with other sectors' contributions remaining relatively stable. In 1999, real GDP growth and inflation are expected to slow to about 4 percent and 2 percent, respectively. The overall public sector surplus is expected to increase slightly about 1 percent of GDP.